Cancer Diagnostics: A Novel Blood‐Based Colorectal Cancer Diagnostic Technology Using Electrical Detection of Colon Cancer Secreted Protein‐2 (Adv. Sci. 11/2019). Issue 11 (4th June 2019) - Jeun, Minhong; Lee, Hyo Jeong; Park, Sungwook; Do, Eun‐ju; Choi, Jaewon; Sung, You‐Na; Hong, Seung‐Mo; Kim, Sang‐Yeob; Kim, Dong‐Hee; Kang, Ja Young; Son, Hye‐Nam; Joo, Jinmyoung; et al.
Abstract : In article number1802115, Kwan Hyi Lee, Seung‐Jae Myung, and co‐workers successfully develop an electric field effect colorectal sensor (E‐FECS) equipped with a thin film transistor‐chipset, a disposable multiwell gate, and an integrated measurement box to detect colon cancer secreted protein‐2 (CCSP‐2) in blood samples from human colorectal cancer (CRC) patients. The E‐FECS system has the potential as a diagnostic tool for postoperative monitoring and early detection of CRC.